1993
DOI: 10.1007/bf01983205
|View full text |Cite
|
Sign up to set email alerts
|

The clinical performance of the Multiload IUD. I. The influence of the endometrial cavity length

Abstract: Nine hundred and seventy-four cavimetries were performed using Kurz's Cavimeter prior to the insertion of a MLCu375 IUD. In this trial, we studied the endometrial cavity length of these women. Results of the cavimetries were correlated to IUD complications to determine which uterine sizes were associated with IUD side-effects. The expulsion rate was higher for women with an endometrial cavity length equal to or greater than 45 mm (p < 0.01) for one and two years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…However, asymptomatic IUD displacements are only detected, if regular sonographic controls of the IUD position are performed. Previous expulsion of an IUD, young age, hypermenorrhea, nulliparity and uterus sounding 9.0 cm are associated with a higher rate of IUD dislocations [2,6,7]. Most downward migrations of IUD are thought to occur within 6 weeks after insertion [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, asymptomatic IUD displacements are only detected, if regular sonographic controls of the IUD position are performed. Previous expulsion of an IUD, young age, hypermenorrhea, nulliparity and uterus sounding 9.0 cm are associated with a higher rate of IUD dislocations [2,6,7]. Most downward migrations of IUD are thought to occur within 6 weeks after insertion [8].…”
Section: Introductionmentioning
confidence: 99%
“…16 The study demonstrated that when the difference between uterine cavity length and the maximum length of MLCu375 was 10 mm or greater, the expulsion rate increased significantly (P > 0.01). Our study provided additional evidence on the association of LUC with expulsion or displacement in the Chinese population.…”
Section: Discussionmentioning
confidence: 85%
“…We categorised women into two groups using 45 mm as the cut-off point of LUC, based on Castro's study, 16 when analysing the effect of LUC among MLCu375 users. However, according to the literature there are no widely accepted cut-off points of LUC for TCu380A, of LTD for either model, and of D1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations